The Differences Influence of Health Education Demonstration and Video Methods on Knowledge, Attitude, and Ability of Adolescent Practices about the Breast Self-Examination - Achmad Wahdi; Dewi Retno Puspitosari; Eppy Setiyowati (Master of Public Health Program Institut Ilmu Kesehatan STRADA Indonesia, 2020)
Background: Breast self-examination is very important for women and it would be better if the teenagers already have the knowledge and practical ability to realize. Therefore breast self-examination is very important to do in adolescents as early detection of breast cancer. The study aims to determine the differences in the influence of health education demonstration methods and video screenings on the knowledge, attitudes, and abilities of youth practice about BSE. Methods: The research design used queasy-experimental, the population of the study at Darul Ulum 1 High School was 325 respondents, and a sample of 60 respondents (demonstration group n= 30, video playback group n = 30) were taken using the Stratified Random Sampling technique. Statistical tests using Wilcoxon and Mann Whitney with significance level α ≤ 0.05. Results: The results showed there was an influence of health education demonstration and video playback methods on knowledge, attitudes, and practice abilities with a value of p= 0,000 (p<α), there were differences in the influence of health education demonstration methods and video playback on knowledge, attitudes and practice abilities with p value= 0.001 (p<α). Discussion: Demonstration and video playback methods can improve knowledge, attitudes, and practice abilities compared to before being given treatment, so adolescents experience behavioral changes and expect health values ​​to be well embedded, health status to be good, and finally teens able to be independent in health problems